1985
DOI: 10.1002/j.1460-2075.1985.tb04118.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction between a transcription factor and the upstream element of the adenovirus-2 major late promoter.

Abstract: Stimulation of in vitro transcription mediated by the upstream element of the adenovirus-2 major late promoter (Ad2MLP) involves its recognition by a specific trans-acting factor present in a HeLa whole-cell extract. DNase I footprinting and dimethylsulfate methylation protection experiments were used to determine, at the nucleotide level, upstream sequences which interact with this transcription factor. The ability of upstream element mutants to bind the transcription factor correlates directly with the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
132
0
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(140 citation statements)
references
References 47 publications
(82 reference statements)
7
132
0
1
Order By: Relevance
“…Our data point strongly to a USF heterodimer being the predominant factor that binds to this particular E-box. USF was originally identi®ed as a human cellular factor which bound to an E-box motif in the adenovirus major late promoter and which stimulated transcription in in vitro assays (Carthew et al, 1987;Miyamoto et al, 1985;Sawadogo and Roeder, 1985). Bendall and Molloy (1994) performed a detailed analysis of E-box¯anking sequences in order to identify the determinants for Myc/Max versus USF speci®city.…”
Section: Discussionmentioning
confidence: 99%
“…Our data point strongly to a USF heterodimer being the predominant factor that binds to this particular E-box. USF was originally identi®ed as a human cellular factor which bound to an E-box motif in the adenovirus major late promoter and which stimulated transcription in in vitro assays (Carthew et al, 1987;Miyamoto et al, 1985;Sawadogo and Roeder, 1985). Bendall and Molloy (1994) performed a detailed analysis of E-box¯anking sequences in order to identify the determinants for Myc/Max versus USF speci®city.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that USF bound the HLH-OB2 enhancer was somewhat unexpected since USF has a fairly well established consensus binding site of CACGTG (25)(26)(27), which differs in the central dinucleotide from the CT/CGRP HLH-OB2 HLH motif of CAGCTG. This latter sequence is preferably recognized by the E12 and myoD class of HLH proteins, not the USF proteins (46).…”
Section: Activity Of the Ct/cgrp Enhancer In The Context Of Flanking mentioning
confidence: 99%
“…The E12/E47 and ITF-2 proteins have been shown to functionally interact with homeodomain proteins to help direct cell-specific gene expression (22)(23)(24). The USF proteins were initially identified as upstream stimulatory factors that control the adenovirus major late promoter (25)(26)(27). Since then, USF binding sites have been found in a number of cellular genes (28 -33).…”
mentioning
confidence: 99%
“…Altogether, these studies have identified three promoter elements; the upstream activating element (UAE) centered at position -63 to -52, the TATA box located at position -31 to -25, and the initiator at position -6 to + 4. Sawadogo and Roeder (1985) and others (Carthew et al 1985;Miyamoto et al 1985) have described a cellular factor, upstream stimulatory factor (USF, or MLTFI or UEF) that both stimulates transcription of the AdML promoter up to 10-fold in vitro and binds to an upstream element that is essential for this stimulation. Glycerol gradient sedimentation studies indicate a size of 45-60 kD for USF (Chodosh et al 1986;Moncollin et al 1986).…”
mentioning
confidence: 99%